Qur’anic Reading Support as an Inclusive Student Service: Preliminary Qualitative Evidence from Tahsin in an Indonesian Public Junior Secondary School - M. Rafi Rizqullah; J.M. Ekafitrianda (WISE Pendidikan Indonesia, 2026)
This study aims to examine how a school-based Qur’anic recitation improvement program (tahsin) functions as an inclusive student-support service for Arabic letter articulation (makhārij al-ḥurūf) in an Indonesian public junior secondary school. A qualitative descriptive case analysis was undertaken using the documented preliminary evidence available for Grade IX D at SMP Negeri 7 Tanjung Jabung Timur: the program schedule, classroom observation mapping, and pedagogical documentation. The analysis identified a 30-minute pre-Dhuhr routine structured around whole-class reading, teacher modeling, corrective repetition, and selective small-group support. The most salient difficulties were clustered around perceptually or articulatorily close phonemes: sīn /s/, shīn /ʃ/, and ṣād /sˤ/; tāʾ /t/ and ṭāʾ /tˤ/; and dhāl /ð/, zāy /z/, and ẓāʾ /ðˤ/. Three interacting constraints limited individualized correction: compressed instructional time, the practical demands of a full class, and linguistic diversity shaped by Javanese, Buginese, and Malay speech backgrounds. Tahsin is therefore best understood not only as technical tajwid instruction, but also as a human-centered support practice that can expand equitable participation and confidence in Islamic Religious Education (IRE). Findings are bounded to preliminary case evidence and do not establish causal effects.